Implemented Interventions at the Naef K. Basile Cancer Institute to Protect Patients and Medical Personnel From COVID Infections: Effectiveness and Patient Satisfaction - El Cheikh, Jean; El Warrak, Samantha; Ghaoui, Nohra; Al Chami, Farouk; Shahbaz, Maya; Chehayeb, Sarah; Saghir, Nagi; Bazarbachi, Ali; Taher, Ali (Frontiers in Oncology, 2021)
Background The Coronavirus Disease 2019 (COVID-19) was declared a pandemic by WHO in March 2020. The first case of COVID-19 was identified in Lebanon on the 21st of February 2020, amid a national economic crisis. As the numbers of cases increased, ICU admissions and mortality rose, which led hospitals across Lebanon to take certain safety measures to contain the virus. The Naef K. Basile Cancer Institute (NKBCI) at the American University of Beirut Medical Center handles oncology outpatient visits and outpatient treatment protocol infusions. The aim of this study is to evaluate the efficacy of the safety measures put forth by the NKBCI early in the pandemic. Methods Oncology patients are amongst the immunosuppressed population, who are at greatest risk of contracting COVID-19 and consequently suffering its complications. In this manuscript, we evaluated the precautionary measures implemented at the NKBCI of AUBMC from March 1st to May 31st of 2020, by surveying oncology patients on the telephone who had live and virtual appointments in both the oncology outpatient clinics and infusion unit. We conducted a prospective study of 670 oncology patients who had appointments at the NKBCI during this period and used their answers to draw responses about patient satisfaction towards those safety measures. Results Our results involved 387 responses of oncology patients who visited the NKBCI during the period of March 1st to May 31st of 2020. 99% of our respondents gave a rating of good to excellent with these new measures. The option of online consultation was given to 35% in the hematology group compared to 19% in those with solid tumors (p=0.001). From the total, 15% of patients opted for the telemedicine experience as a new implemented strategy to provide patient-centered medical care. Of this group of patients, 22% faced problems with connectivity and 19% faced problems with online payment. Conclusion NKBCI was competent in following the WHO guidelines in protecting the oncology patient population. Feedback collected from the surveys will be taken into account by the committee of the NKBCI to develop new safety measures that can better control viral spread while providing patient-centered medical care.